Bioinformatics Analysis of Disc Large Homolog-4 (DLG-4) As Parameters in Neuroplasticity - Eka Febri Zulissetiana; Irfannuddin Irfannuddin (Sriwijaya Journal of Medicine, 2023)
Disc Large Homolog-4 (DLG-4), also known as Post Synaptic Density 95 (PSD95) is believed to have an important role in the function and organization of the synapse. DLG-4 is the main protein structure at the synapse that is able to bind to various molecules on the surface of the postsynaptic membrane. This review aims to determine the biomolecular characteristics of DLG-4 and the role of DLG-4 as an important parameter in neuroplasticity. Biomolecular characteristic analysis was obtained through various bioinformatics websites namely NCBI, PROTPARAM, TMHMM, PEPTIDE CUTTER, NETNGLYC, TARGETP and KEGG PATHWAY. The DLG-4 gene is located on chromosome 17p13.1 and has 25 exon. The DLG-4 protein consists of 764 amino acids with a molecular weight of 80.47 kDa. DLG-4 has a structure of 3 N-terminal PDZ domains, a Src Homology 3 (SH3) domain and a guanilate kinase-like C-terminal domain. This protein has a stability score of 48.61. The aliphatic index is 85.42. DLG-4 is found inside, outside, and on transmembranes, as determined by THMM. There are 37 enzymes that are predicted to be able to split the DLG-4 protein. The DLG-4 protein shows 3 potential sites of glycosylation of amino acids. The target location of the DLG-4 protein is mostly in other locations (other = 0.6556), secretory pathway (0.3328), and only slightly in mitochondria (0.0116). The DLG-4 protein is strongly associated with the glutamatergic system in postsynaptic neurons. The glutamatergic system is concerned with the molecular mechanism of memory development and cognitive function, long-term potentiation (LTP). These findings support the fact that DLG-4 protein plays a role in neuroplasticity mechanisms in the brain.